(untitled) (Res Medica, 2014)
• Principles and Practice of Medical Computing: ￡3. Churchill Livingstone. L. G. Whitby and W. Lutz. • Textbook of Medical Treatment, 12th Edition, ￡4.25. Longman Group Ltd., 1971. Edited Alstead, MacGregor and Girdwood. • An Introduction to Clinical Research. £1.50 Churchill Livingstone. W. P. Small and Urban Krause. • The Significance of Physical Signs in Medicine (1st Edition). £2.25. H. K. Lewis and Co., Ltd., Peter Mills. • Jamieson’s Illustrations of Regional Anatomy, Section V II, Lower Limb: Livingsone: ￡1. Revised by Robert Warmsley and T. R. Murphy, 9th Edition. • Statistics in Small Doses. ￡2. A Livingstone Medical Text. Churchill Livingstone. W. M. Castle.